Studi etnobotani ritual adat Babarit pada masyarakat Dusun Lengkong Kabupaten Majalengka - Sari, Arum; Cahyanto , Tri (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Lengkong Hamlet community is a community that is still thick with cultural customs, one of which is the Babarit traditional ritual. The ritual involves the use of natural resources including various types of plants. The purpose of this study was to identify the types of plants used in the Babarit ritual in Lengkong Hamlet, Nunukbaru Village, Maja District, Majalengka Regency. The research method uses qualitative and quantitative descriptive analysis techniques. Qualitative data were obtained from interviews related to respondents’ knowledge of plants for the Babarit ceremony, while quantitative data were obtained by calculating the percentage of plant organs used as ritual materials. Based on the research results, there were 24 families and 43 species of plants used. The use of plant organs includes seeds (9%), flowers (17%), stems (2%), roots (2%), fruits (42%), tubers (17%), and sap (2%). Plant materials used in the Babarit ritual were obtained from gardens (44%), yards (30%) and markets (26%). The way plants are used in the Babarit traditional ritual varies in each procession, procedure and different functions and meanings. The use of plants has a conservation meaning for the environment, namely planting various types of plants that are widely used as an effort to avoid extinction and to maintain sustainability.